Constraining competing models of dark energy with cosmological observations - Pavlov, Anatoly (Kansas State University, 2015)
The last decade of the 20th century was marked by the discovery of the accelerated expansion of the universe. This discovery puzzles physicists and has yet to be fully understood. It contradicts the conventional theory of gravity, i.e. Einstein’s General Relativity (GR). According to GR, a universe filled with dark matter and ordinary matter, i.e. baryons, leptons, and photons, can only expand with deceleration. Two approaches have been developed to study this phenomenon. One attempt is to assume that GR might not be the correct description of gravity, hence a modified theory of gravity has to be developed to account for the observed acceleration of the universe’s expansion. This approach is known as the ”Modified Gravity Theory”. The other way is to assume that the energy budget of the universe has one more component which causes expansion of space with acceleration on large scales. Dark Energy (DE) was introduced as a hypothetical type of energy homogeneously filling the entire universe and very weakly or not at all interacting with ordinary and dark matter. Observational data suggest that if DE is assumed then its contribution to the energy budget of the universe at the current epoch should be about 70% of the total energy density of the universe. In the standard cosmological model a DE term is introduced into the Einstein GR equations through the cosmological constant, a constant in time and space, and proportional to the metric tensor g[subscript]mu[subscript]nu. While this model so far fits most available observational data, it has some significant conceptual shortcomings. Hence there are a number of alternative cosmological models of DE in which the dark energy density is allowed to vary in time and space.
Keywords: Astronomy; Astrophysics; Physics; Theoretical physics; Quantum physics; Statistics; Cosmology; Numerical Simulations; Data Analysis; Theoretical Physics (0753)